The global economic crisis: An opportunity for strengthening Asia's social protection systems? - Mukul G. Asher (Asian Development Bank Institute (ADBI), 2010)
The current global economic crisis has led to greater prominence for the issue of strengthening social protection systems in Asia. This paper analyzes the key factors determining and the possible avenues for strengthening social protection systems in Asia. The choice of an appropriate combination of avenues depends on the initial starting point, public policy objectives, institutional, fiscal, and other capabilities. Following introductory remarks, Section 2 discusses demographic and labor market trends in Asia. It stresses that rapid ageing and large, informal labor markets pose challenges for Asian social protection systems, while making the role of the state even more essential. This is followed in Section 3 by an overview of social security systems in Asia. The key point is that while there are fairly elaborate social security programs in Asia, primarily for formal sector employees, this does not necessarily imply that the schemes are well designed, have wide coverage, or are financially sustainable. Section 4 discusses four general avenues to strengthening social protection systems. These emphasize greater professionalism, parametric and systemic reforms, social assistance, and social pensions, as well as others such as microfinance institution-initiated pensions. The final section provides concluding observations. The global economic crisis provides a potential opportunity for strengthening social protection systems. However, the construction of multitiered social protection systems will require much greater professionalism, experimentation, political and organizational leadership, and vision.
Keywords: H55; H87; J11; J18; J21; J26; 330; Soziale Sicherung; Bevölkerungsentwicklung; Sozialpolitik; Asien